Decision Support System For Determining Recipients Of Home Improvement Assistance Using The Weighted Product Method In Siantar Narumonda District - manullang, Jontinus; Lubis, Harmoko; Nduru, Sastra Wandi; Situmorang, Sutrisno (Marcha Institute, 2024)
A house is a building that functions as a residence or residence and a means of fostering a family. In rural areas there are still many residents' houses that are uninhabitable and this is caused by the standard of living of people who still live modestly and have incomes below the average, these conditions make many residents' houses uninhabitable that need to be renovated through house renovation assistance. Decision making is a system that is able to provide both problem-solving abilities and communication skills for semi-structured problems. This research system aims to design a system for determining recipients of home surgery assistance using the method, Weighted product which is one of the methods in SPK which uses a weighting method with a rating of an appraisal variable. The programming language used in making the system is PHP with a MySQL database. The results of the implementation of the system that has been made show that Parasman (A1), Hendra (A9), Ferdinand (A4) are candidates for receiving surgical assistance in Siantar Narumonda District.